20th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2015
DOI: 10.2514/6.2015-3677
|View full text |Cite
|
Sign up to set email alerts
|

Achievements Obtained for Sustained Hypersonic Flight within the LAPCAT-II project

Abstract: The design of hypersonic airbreathing vehicles is a challenging objective due to the intrinsic complexity of propulsion-airframe integration in combination with an engine cycle design able to operate over a wide Mach number range. This is one of the objectives of EC co-funded project LAPCAT-II aiming to reduce antipodal flights to less than 2 to 4 hours. Among the several studied vehicles in the preceding project LAPCAT-I, only aircraft designs for Mach 5 and 8 flights were retained in the present project. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…4,5,6 The internal side of the panels have an insulation facing the liquid hydrogen (LH2) cryogenic tank at 20 K. Different flight Mach numbers from Mach 4 to Mach 10 were explored at 2 different dynamic pressures, i.e. 25 kPa and 50 kPa.…”
Section: Basic Thermal Methodologymentioning
confidence: 99%
“…4,5,6 The internal side of the panels have an insulation facing the liquid hydrogen (LH2) cryogenic tank at 20 K. Different flight Mach numbers from Mach 4 to Mach 10 were explored at 2 different dynamic pressures, i.e. 25 kPa and 50 kPa.…”
Section: Basic Thermal Methodologymentioning
confidence: 99%
“…from Brussels to Sydney, to less than 2 to 4 hours resulting in a Mach 5 and Mach 8 configuration. [27][28][29] To fulfill this mission, a hypersonic aircraft with near antipodal range (20,000 km) is required. The corresponding trajectories are provided in figure 2a.…”
Section: Field Of Application Of Ultrasonically Absorptive Tps Mamentioning
confidence: 99%
“…n the basis of various conceptual vehicle designs within LAPCAT-II [1][2] [3], it was demonstrated that a hypersonic vehicle with 300 PAX on-board can achieve an antipodal flight e.g. from Brussels to Sydney at a cruise speed of Mach 8.…”
Section: Introductionmentioning
confidence: 99%